Investigating the fatigue and fracture behaviour of advanced composite materials in aerospace structures (Journal of Advances and Scholarly Researches in Allied Education, 2025)
In order to simulate the intricate stress distribution into important locations, Full-scale components, undergo fatigue testing. Parts of a larger structural system, such as sub-assemblies, are sometimes the subjects of these tests. Lastly, they are often performed on little samples with the purpose of collecting fatigue data. This data shows how a material has been affected by factors including stress level, surface preparation, environment, and loading history.